If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3y + 5)(6y + -1) = 0 Reorder the terms: (5 + 3y)(6y + -1) = 0 Reorder the terms: (5 + 3y)(-1 + 6y) = 0 Multiply (5 + 3y) * (-1 + 6y) (5(-1 + 6y) + 3y * (-1 + 6y)) = 0 ((-1 * 5 + 6y * 5) + 3y * (-1 + 6y)) = 0 ((-5 + 30y) + 3y * (-1 + 6y)) = 0 (-5 + 30y + (-1 * 3y + 6y * 3y)) = 0 (-5 + 30y + (-3y + 18y2)) = 0 Combine like terms: 30y + -3y = 27y (-5 + 27y + 18y2) = 0 Solving -5 + 27y + 18y2 = 0 Solving for variable 'y'. Factor a trinomial. (-5 + -3y)(1 + -6y) = 0Subproblem 1
Set the factor '(-5 + -3y)' equal to zero and attempt to solve: Simplifying -5 + -3y = 0 Solving -5 + -3y = 0 Move all terms containing y to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + -3y = 0 + 5 Combine like terms: -5 + 5 = 0 0 + -3y = 0 + 5 -3y = 0 + 5 Combine like terms: 0 + 5 = 5 -3y = 5 Divide each side by '-3'. y = -1.666666667 Simplifying y = -1.666666667Subproblem 2
Set the factor '(1 + -6y)' equal to zero and attempt to solve: Simplifying 1 + -6y = 0 Solving 1 + -6y = 0 Move all terms containing y to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -6y = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -6y = 0 + -1 -6y = 0 + -1 Combine like terms: 0 + -1 = -1 -6y = -1 Divide each side by '-6'. y = 0.1666666667 Simplifying y = 0.1666666667Solution
y = {-1.666666667, 0.1666666667}
| 4+Y=18-Y | | 1.49+a=2.99 | | 16(t-5)+5t=7(3t+3)-11 | | 2+3(15-2*3)2= | | 25c+10c=b | | 4x+3=3x+30 | | (1+v)(3v+7)=0 | | V=L*M*H | | 8+9s-2=5s+48-3s | | X-2(5)=X+7 | | 500+Y+4=554 | | x^4+4x-12=0 | | (5)X-2=X+7 | | 6x+14+2x-28=90 | | -25-4n=8(6n+4)-5 | | -18=-6+2q | | 39-8r=-3(1+3r)-5r | | 7x-17+2x-19=180 | | 2y-x=6x-8 | | 55x^2-233x+126=110 | | -4a+b=29 | | -2n+8=8(5n+1) | | 12-Y=8-2 | | 5(76)-y=170 | | X+150=180 | | 14+x=180 | | (2x-1)*((-2)+(-1x))=4 | | .56=logx | | 25(76)-7y=800 | | f(x)=x^4-50x+7 | | 6x+12+x+21=180 | | -14+2n=-4(n+5) |